Maple phylogeny and biogeography inferred from phylogenomic data. Issue 6 (22nd September 2019) - Li, Jianhua; Stukel, Mark; Bussies, Parker; Skinner, Kaleb; Lemmon, Alan R.; Lemmon, Emily Moriarty; Brown, Kenneth; Bekmetjev, Airat; Swenson, Nathan G.
Abstract: Acer (the maple genus) is one of the diverse tree genera in the Northern Hemisphere with about 152 species, most of which are in eastern Asia. There are roughly a dozen species in Europe/western Asia and a dozen in North America. Several phylogenetic studies of Acer have been conducted since 1998, but none have provided a satisfactory resolution for basal relationships among sections of Acer . Here we report the first well‐resolved phylogeny of Acer based on DNA sequences of over 500 nuclear loci generated using the anchored hybrid enrichment method and explore the implications of the robust phylogeny for Acer systematics and biogeography. Our phylogenetic results support the most recent taxonomic treatment of Acer by de Jong with some modifications; section Pentaphylla may be expanded to include section Trifoliata, and A. yangbiense may be included in section Lithocarpa . Sections Spicata, Negundo, Arguta, and Palmata form a clade sister to the rest of the genus where sections Glabra and Parviflora comprise the first clade followed by section Macrantha, sections Ginnala, Lithocarpa, Indivisa, sections Platanoidea and Macrophylla, section Rubra, section Acer, and section Pentaphylla . Monotypic sections Glabra and Macrophylla in North America are sister to the Japanese section Parviflora and Eurasian section Platanoidea, respectively. Ancestral area inferences using statistical dispersal and vicariance analysis (S‐DIVA) and dispersal and extinction cladogenesis (DEC) methods suggest that Asia might be the most likely ancestral area of Acer as proposed by Wolfe and Tanai and molecular dating using Bayesian evolutionary analysis by sampling trees (BEAST) indicate that section diversifications of Acer might have completed largely in the late Eocene and the intercontinental disjunctions of Acer between eastern Asia and eastern North America formed mostly in the Miocene.